2021
DOI: 10.1089/wound.2020.1175
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Mesenchymal Stromal Cells in Regenerative Medicine: State of Play, Current Clinical Trials, and Future Prospects

Abstract: Significance: Wound healing is a complex process involving pain and inflammation, where innervation plays a central role. Managing wound healing and pain remains an important issue, especially in pathologies such as excessive scarring (often leading to fibrosis) or deficient healing, leading to chronic wounds. Recent Advances: Advances in therapies using mesenchymal stromal cells offer new insights for treating indications that previously lacked options. Adiposederived mesenchymal stromal cells (AD-MSCs) are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 238 publications
0
25
0
Order By: Relevance
“…Wound healing is a complex process involving pain and inflammation, proliferation, and excessive scarring (often leading to fibrosis). 42 Then, we found that S100A4 silencing promoted the differentiation of rCSCs following corneal alkali burn into the cornea. During the healing process of corneal stromal cells, the activation of the TGF-β system makes corneal cells transform into myofibroblasts.…”
Section: Discussionmentioning
confidence: 93%
“…Wound healing is a complex process involving pain and inflammation, proliferation, and excessive scarring (often leading to fibrosis). 42 Then, we found that S100A4 silencing promoted the differentiation of rCSCs following corneal alkali burn into the cornea. During the healing process of corneal stromal cells, the activation of the TGF-β system makes corneal cells transform into myofibroblasts.…”
Section: Discussionmentioning
confidence: 93%
“… 2019 ; Al-Ghadban and Bunnell 2020 ; Laloze et al. 2021 ). However, several challenges have to be addressed related to the safety and efficacy of AdMSCs in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…During the healing process, numerous distinct cells, especially stem cell are activated, recruited into the wound, and secreted various growth factors and cytokines [4][5][6]. With the development of regenerative medicine, stem cells are becoming new strategies for effective wound treatment [7,8].…”
Section: Introductionmentioning
confidence: 99%